Impact of Hurricane Ian (2022) on Karenia brevis Bloom on the West Florida Shelf - Yuren Chen; Ming Li (Geophysical Research Letters)
Abstract Blooms of toxigenic Karenia brevis are a major concern to public health and marine ecosystems on the West Florida Shelf. Hurricanes and tropical storms can discharge huge amounts of terrestrial nutrients into coastal oceans over a short time and have been linked to large plankton blooms, but the underlying mechanisms for the bloom generation are not well understood. In 2022, Hurricane Ian generated extensive river plumes laden with nutrients, followed by a large K. brevis bloom that lasted for six months. Analysis using a coupled hydrodynamic‐biogeochemical model showed that Hurricane Ian drove the bloom in two ways. First, northerly winds on the western half of Ian generated coastal upwelling and onshore bottom currents that transported subsurface K. brevis cells toward the coast. Second, a substantial amount of the riverine nutrients remained after the initial diatom bloom and were dispersed widely, creating a favorable condition for the slow‐growing K. brevis.